Picture Perfect : Life in the Age of the Photo Op - New Edition - Adatto, Kiku, 1947- (Book collections on Project MUSE., 2008)
We say the camera doesn't lie, but we also know that pictures distort and deceive. In Picture Perfect, Kiku Adatto brilliantly examines the use and abuse of images today. Ranging from family albums to Facebook, political campaigns to popular movies, images of war to pictures of protest. Adatto reveals how the line between the person and the pose, the real and the fake, news and entertainment is increasingly blurred. New technologies make it easier than ever to capture, manipulate, and spread images. But even in the age of the Internet, we still seek authentic pictures and believe in the camera.